Associations between major life events and adherence, glycemic control, and psychosocial characteristics in teens with type 1 diabetes1. Issue 1 (19th April 2017) - Commissariat, Persis V.; Volkening, Lisa K.; Guo, Zijing; ElBach, Jessica L.; Butler, Deborah A.; Laffel, Lori M.
Abstract : Aims: This cross‐sectional study assessed the type of major life events occurring in a contemporary sample of teens with type 1 diabetes and the association between event frequency and demographic, diabetes management, and psychosocial characteristics. Methods: Parents of 178 teens completed the Life Events Checklist to report major events teens had experienced in the last year: 42% experienced 0 to 1 event (n = 75), 32% experienced 2 to 3 events (n = 57), and 26% experienced 4+ events (n = 46). Teens and parents completed validated measures of treatment adherence, diabetes‐specific self‐efficacy, quality of life, and diabetes‐specific family conflict. Parent‐youth interview and chart review provided demographics and diabetes management data. Results: Mean number of events/teen was 2.6 ± 2.7 (range = 0‐15). The most common events were "Hospitalization of a family member" (24%), "Getting a bad report card" (20%), "Serious arguments between parents" (19%), and "Serious illness/injury in a family member" (19%). Compared with teens experiencing 0 to 1 event, teens experiencing 4+ events were less likely to have married parents ( P = .01) and a parent with a college degree ( P = .006). Teens with 4+ events had significantly poorer adherence ( P = .002 teen, P = .02 parent), lower self‐efficacy ( P = .03 teen, P < .0001 parent), poorer quality of life ( P < .0001 teen, P < .0001 parent), and more conflict ( P = .006 teen, P = .02 parent) than teens with fewer events. In a multivariate model ( R 2 = 0.21, P < .0001) controlling for demographic and diabetes management characteristics, fewer events was associated with lower A1c ( P = .0009). Conclusions: Occurrence of more major life events was associated with poorer diabetes care and A1c and more negative psychosocial qualities in teens with type 1 diabetes.